RESOURCE-EFFICIENT ALLOCATION HEURISTICS FOR MANAGEMENT OF DATA CENTERS FOR CLOUD COMPUTING - Litvinov, Vitaliy; Matsueva, Karyna (Proceedings of National Aviation University (archive), 2014)
Survey of research in resource-efficient computing and architectural principles forresource-efficient management of Clouds are offered in this article. Resource-efficient resource allocation policies and scheduling algorithms considering QoS expectations and power usage characteristics of the devices are defined.